Enhancing cycling stability in Li-rich Mn-based cathode materials by solid-liquid-gas integrated interface engineering. (15th June 2022) - Guo, Weibin; Zhang, Yinggan; Lin, Liang; He, Wei; Zheng, Hongfei; Lin, Jie; Sa, Baisheng; Wei, Qiulong; Wang, Laisen; Xie, Qingshui; Peng, Dong-Liang
Abstract: The specific capacity of Li-rich Mn-based cathode materials (LRM) can be enhanced by the oxidation of lattice oxygen at high voltages. Nevertheless, an irreversible oxygen loss emerges with cycling, triggering interlocking surface/interface issues and thereby the fast deterioration of cycling performance. Herein, a solid-liquid-gas integrated surface/interface modification method is presented to form a CEI preconstruction layer and defective heterostructure on the surface/interface of LRM material to improve its cycling stability greatly. The CEI preconstruction layer can effectively anchor on the surface/interface of LRM primary and secondary particles to induce a thin and exceptionally stable CEI layer during cycling, and then mitigate the TM dissolution and strengthen the stability of surface lattice oxygen. The introduced defective heterostructure can reduce the charge transfer resistance. As a result, the designed LRM cathode displays a high reversible capacity of 315 mAh g −1 at 0.1 C as well as high capacity retention of 83.3% at 1 C after 500 cycles. Outstanding voltage stability with a retention of 91.5% is achieved at 5 C after 500 cycles. This work opens an attractive path in manipulating the surface/interface stability of LRM to enhance its cycling performance for high-energy-density Li-ion batteries. Graphical abstract: The table of contents entry: A solid-liquid-gas integrated interface engineering is presented to construct a CEI preconstruction layer on the surface and defective heterostructure in the subsurface region of Li-rich cathode. These delicate designs can reduce the interfacial side reaction, mitigate the TM dissolution and enhance the diffusion rate of lithium-ion, and then strengthen the structure stability effectively. As a result, the modified cathode exhibits outstanding cycling stability. ga1 Highlights: Solid-liquid-gas integrated interface engineering is used to create CEI preconstruction layer and defective heterostructure. The designed CEI preconstruction layer can enhance the surface stability of cathode material. The introduced defective heterostructure can reduce the charge transfer resistance. The elaborately designed Li-rich cathode displays outstanding cycling stability.